KAKSA Orang Tua Siswa TK : Komunitas Anti Kekerasan Seksual pada Anak - Ira Paramastri (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
Currently, primary prevention efforts for child sexual abuse (CSA) are mostly done as a general education program for children at school. The program is criticized for placing the responsibility of child protection solely on the children and rarely involves family, community, and children’s surrounding neighborhood. This study aimed to examine CSA psychoeducational prevention toward kindergarteners parents’ knowledge after intervention in the form of psychoeducational leaflets and booklets. The study was a quasi-experimental study with the one-group pretest-posttest design. Twenty-six parents of kindergarteners participated in the study. Instruments used for the study was the CSA knowledge test. Quantitative analysis was used to describe the difference between kindergarteners parents’ knowledge before and after the program (p=0.006, p<0.05). Psychoeducation with booklet and leaflet was able to improve kindergarteners parents’ knowledge on CSA prevention.